Time to critical overcrowding of Manitoba swine barns in the event of restriction on animal movement - Bargen, Leeanne L. (2002)
Canada maintains a stamping-out policy for control of foreign animal disease. Integral to stamping out, there are obligatory animal movement restrictions that, over time, can result in severe animal welfare problems. The purpose of this study was to estimate the time to critical overcrowding in a sample of Manitoba swine farms, if they were placed under movement restriction. Time to critical overcrowding in both static and dynamic populations was estimated by modeling swine growth and projecting anticipated on-farm stocking density through time and comparing it with a standard maximal stocking density. The time to critical overcrowding of 15 isowean piglet production units was 0.66 ± 0.88 weeks. On average, 7 isolated nursery facilities reached critical overcrowding in 52 ± 14 days and 5 farrow-to-finish operations reached critical overcrowding in 43 ± 18 days. Animal welfare concerns should be included in contingency plans to control foreign animal disease.